Hydroxyl radical induced structural changes of collagen. Issue 2 (2007) - Xiao Xiao, Helan Helan; Cai Cai, Guoping Guoping; Liu Liu, Mingyao Mingyao
Abstract : Extracellular matrix (ECM) plays an important role in cell differentiation, growth, migration and apoptosis. Collagen is the most abundant protein family in vivo, but its function has still not been clearly defined yet. Reactive oxygen species (ROS) have a central role in oxidative cell stress. Electron spin resonance (ESR) spectroscopy indicates that type I collagen could uniquely scavenge hydroxyl radicals in dose- and time-dependent manner; whereas BSA and gelatin (a denatured collagen) have no such an effect. However, the mechanism by which type I collagen scavenges hydroxyl radicals is different from that of GSH, a well-known free radical scavenger. Using a new method, two-dimensional FTIR correlation analysis, for the first time, we show that the order of functional group changes of type I collagen in this process is amide I earlier than amide II than amide III than –CH– than ν (C=O). The results indicates that the structure of the main chain of collagen changed first, followed by more residue group ν (C=O) exposed to hydroxyl radicals. The reaction with the carbonyl group in collagen causes the hydroxyl free radicals to be scavenged. Therefore, ECM can effectively scavenge ROS under normal physiological conditions. When the proteins of ECM were denatured in the same way as gelatin, they lost their function as a free radical scavenger. All of these results provide new insight into therapy or prevention of oxidative stress, apoptosis and ageing.